Do People Differentially Recall Sexual Information According to Actor Gender? Extending the Confirmation Bias Paradigm. - Marks, Michael J.; Kirkeby, Kimberley M.; Wu, Ashley K. (Sexuality & Culture, 2025)
The sexual double standard (SDS) is the phenomenon whereby sexually active men are evaluated more positively than sexually active women (Marks & Fraley, 2005). The SDS is a well-known phenomenon in contemporary Western society (Endendijk et al., 2020), and evidence suggests that people have a confirmation bias to recall information that is consistent with it, and to not recall that is inconsistent with it (e.g., Marks & Zaikman, 2023). However, the sexual information given to participants in past recall studies was not pre-tested to be of equal valence. To address this limitation, we had 317 participants read a vignette about a sexually active hypothetical man or woman that contained an equal amount of pre-equated positive and negative comments about the target person, then attempt to recall valenced information from the vignette. Participants recalled more negative than positive information about sexually active people, but this effect was stronger for the female target person. Participants further falsely recalled more positive comments about the male than the female target person, and more positive than negative comments about the male target person, partially supporting hypotheses that participants would recall more information that was consistent with an SDS. The current results suggest using non-evaluative paradigms in SDS research and that the SDS may be highly driven by gender stereotypes and sexual norms.